2018
DOI: 10.1111/1756-185x.13261
|View full text |Cite
|
Sign up to set email alerts
|

Screening for latent tuberculosis infection among patients with rheumatoid arthritis in the era of biologics and targeted synthetic disease‐modifying anti‐rheumatic drugs in India, a high‐burden TB country: The importance of Mantoux and Quantiferon‐TB Gold tests

Abstract: Combined a-TST with QFTG testing gave 43% positivity among RA patients, which is close to the reported ~ 40% Mantoux positivity in the general population. Therefore, this method for the screening of LTBI in Indian patients with RA being considered for tumor necrosis factor alpha treatment could be satisfactory for offsetting TB flare. It may apply to other high-burden TB countries around the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
2
1
0
1
Order By: Relevance
“…A TBNET study [36] has also shown that TST cut-off of 10 mm is most appropriate for the diagnosis of LTBI in RA patients since loss in sensitivity by increasing the cut-off from 5 to 10 mm is marginal while there is substantial gain in specificity. The rate of TST positivity in our patients (30.8%) was comparable to that (30%) in another study on RA patients from India, despite the authors choosing to use a double strength (10 TU) of PPD [37].…”
Section: Discussionsupporting
confidence: 82%
“…A TBNET study [36] has also shown that TST cut-off of 10 mm is most appropriate for the diagnosis of LTBI in RA patients since loss in sensitivity by increasing the cut-off from 5 to 10 mm is marginal while there is substantial gain in specificity. The rate of TST positivity in our patients (30.8%) was comparable to that (30%) in another study on RA patients from India, despite the authors choosing to use a double strength (10 TU) of PPD [37].…”
Section: Discussionsupporting
confidence: 82%
“…LTBI was seen in more than a third of the patients with SpA, a finding similar to the previously reported for Brazilian ( 17 ), Spanish ( 24 ), South Korean ( 25 ), and Indian patients ( 26 ). We also confirmed that TST positivity was more frequent in the patients with AS than in the patients with PsA ( 17 ) possibly owing to the anergy already known in this latter arthropathy, as observed in rheumatoid arthritis ( 27 ).…”
Section: Discussionsupporting
confidence: 90%
“…Since LTBI has no symptoms, screening is essential. Compared to healthy controls, 40% of Indian RA patients were tuberculin skin test (TST)-positive [ 89 ]. We assume a similar picture due to proximity and demographics.…”
Section: Reviewmentioning
confidence: 99%